CellCelector™ as a platform in isolating primary B cells for antibody discovery. (4th January 2022) - Matochko, Wadim L; Nelep, Constantin; Chen, Weihsu C; Grauer, Stephanie; McFadden, Karyn; Wilson, Vicki; Oxenoid, Kirill
ABSTRACT: The most robust strategy in antibody discovery is the use of immunized animals and the ability to isolate and immortalize immune B-cells to hybridoma for further interrogation. However, capturing the full repertoire of an immunized animal is labor intensive, time consuming and limited in throughput. Therefore, techniques to directly mine the antibody repertoire of primary B-cells are of great importance in antibody discovery. In the current study, we present a method to isolate individual antigen-specific primary B-cells using the CellCellector™ single-cell isolation platform from XenoMouse® (XM) immunized with a recombinant therapeutic protein, EGFR. We screened a subset of CD138+ B-cells and identified 238 potential EGFR-specific B-cells from 1189 antibody-secreting cells (ASCs) and isolated 94 by CellCellector. We identified a diverse set of heavy chain complementarity-determining region sequences and cloned and expressed 20 into a standard human immunoglobulin G1 antibody format. We further characterized and identified 13 recombinant antibodies that engage soluble and native forms of EGFR. By extrapolating the method to all 400 000 CD138+ B-cells extracted from one EGFR immunized XM, a potential 1196 unique EGFR-specific antibodies could be discovered. CellCelector allows for interrogating the B-cell pool directly and isolating B-cells specific to the therapeutic target of interest. Furthermore, antibody sequences recovered from isolated B-cells engage the native and recombinant target, demonstrating the CellCellector can serve as a platform in antibody discovery.